PRIORITY PROGRAM SELECTION OF VILLAGE FUND USING THE K-MEANS METHOD - Ati Sulastri; Siti Khalifah; Dhea Lestari; Dudih Gustian; Muhamad Muslih; Kirishchieva Irina Rafaelevna (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2020)
The allocation of funds is certainly a big village also demands a big responsibility for the village government. In managing public funds, a public sector organization is required to be able to provide accountable financial reports. To achieve the effectiveness of village financial management, a decision support system is needed to assist village officials in determining which village programs will be prioritized. This research focuses on village programs that use village fund allocations. The purpose of this study is to create a decision support system todetermine priority village fund programs using a web-based kmeans clustering algorithm. The k-means clustering algorithm can perform the modeling process without supervision (unsupervised) and is one of the methods that performs data grouping using the partition system. This is in accordance with the desired end result in the form of grouping the village work program into 3 priority levels, where the village road repair program is included in the high-level priority program in cluster 1, the BUMDES program is included in the medium level priority in cluster 2 and the program for the construction of a reservoir for incoming rainwater. in low priority cluster 3. This research was conducted by considering the aspects of urgency and usefulness developed using the programming language PHP version 5 and MySQL database version 3.2.1.